Hubungan Antara Prasangka Sosial dan Kecenderungan Sentripetal-Sentrifugal dengan Ketertarikan Interpersonal Berdasarkan Suku dan Agama di Kota Palopo - Said, Muhazzab Said; Ahsan, Amrul Aysar (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2018)
This research explores the correlation between social prejudice, centripetal-centrifugal tendencies, and interpersonal attraction among individuals from various ethnic and religious backgrounds in Palopo City. The research method used is quantitative, using statistical analysis techniques to test the relationship between these variables. The results showed that there was no significant relationship between racial prejudice, centripetal-centrifugal tendencies, and interpersonal attraction. However, an interesting finding is that there is a very important relationship between social prejudice and centripetal-centrifugal tendencies, where even though social prejudice is high, individuals tend to move closer than away from groups that are considered different. Recommendations for follow-up include further research to understand the deeper factors that mediate this relationship and to identify other factors that influence social interactions. The follow-up plan also provides for developing social intervention strategies that are more effective in promoting tolerance, diversity and positive social integration in the Palopo City community and its surroundings.